Paraspinal neurofibromas and hypertrophic neuropathy in Noonan syndrome with multiple lentigines. Issue 2 (2nd September 2015) - Conboy, Erin; Dhamija, Radhika; Wang, Margaret; Xie, Jing; Dyck, P James; Bridges, Alina G; Spinner, Robert J; Clayton, Amy C; Watson, Robert E; Messiaen, Ludwine; Babovic-Vuksanovic, Dusica
Abstract : Background: Noonan syndrome with multiple lentigines (NSML), formerly known as LEOPARD syndrome, is an autosomal-dominant disorder characterised by lentigines, EKG abnormalities, ocular hypertelorism, pulmonic stenosis, abnormal genitalia, growth retardation and deafness. There is significant clinical overlap between NSML and other disorders that result from dysregulated rat sarcoma/mitogen-activated protein kinase pathway (RASopathies). Except for neurofibromatosis type 1, other RASopathies are not known to be typically associated with neurogenic tumours. Methods and results: We evaluated patients from three families with pigmentary skin lesions, progressive neuropathy, enlarged nerves, massive burden of paraspinal tumours (neurofibroma was confirmed in one patient) and a clinical diagnosis of NSML. All patients had a mutation in the protein tyrosine phosphatase catalytic domain of the PTPN11 gene; two unrelated patients had the p.Thr468Met mutation, while the family consisting of two affected individuals harboured the p.Thr279Cys mutation. Molecular analysis performed on hypertrophic nerve tissue did not disclose a second somatic hit in NF1, PTPN11, NF2 or SMARCB1 genes. Conclusions: Neurogenic tumours and hypertrophic neuropathy are unusual complications of NSML and may be an under-recognised manifestation that would warrant surveillance. Our observation may also have implications for other disorders caused by RAS-pathway dysregulation.